Gogos, yoyos and dodos; Company directors and industry performance - Norburn, David (Cranfield School of Management, 1984)
This research investigates the characteristics of 354 directors of Britain's largest companies. Three sections of independent variables were analysed: those relating to the economic environ; those relating to the domestic environ--family background and educational experiences; those relating to self concept. Directors were categorised according to the economic performance of their industries--GOGOs (industries in growth); YOYOs (industries in turbulence); and DODOs (industries in decline). Several differences emerged between the characteristics of directors and the economic success of their industries for which they were strategically influential.